Introduction to the Musical Composition "Tirtha Nadi" | Pengantar Karya Komposisi Karawitan "Tirtha Nadi" - Gede Risa Sutra Gita; I Ketut Sudhana (GHURNITA: Jurnal Seni Karawitan, 2021)
Tirtha Nadi is a work of new musical compositions of karawitan. In this creation the composer is inspired to take the theme of Tirtha which means the water of life. Through this theme the composer interpretation water as a source of life in terms of the sustainable ecosystem of living things in their natural environment, the composer's aesthetic experience of the natural nuances and beauty of the stylist at that time and lake water flowing in various directions as a source of community life in carrying out various daily activities, which is poured into Part 1, Part 2, and Part 3. The structure is illustrated by patterns arranged based on the theme that is worked on to form a composition music. The musical composition of Tirtha Nadi is a new musical composition that uses media revealed the gamelan Gong Suling and Terompong Beruk instruments. in this composition still uses traditional patterns with developments in melody, rhythm, tempo and techniques. The process of cultivating this new music composition was carried out through stages, namely exploration, improvisation and forming. This creations is 15 minutes long consisting of 3 parts, each of which reveals an aesthetic experience which in this work has the message "preserving water is preserving our lives".